(untitled) (Research, Society and Development, 2022)
The CTSA approach leads us to reflections where scientific knowledge is an important element in the training of the subject for the full exercise of citizenship. In science teaching, as in other subjects that make up the school curriculum, textbooks are a resource of fundamental importance since they represent, in many cases, the most used pedagogical support material by teachers in the classroom. Based on these assumptions, the general objective of this work is to investigate the CTSA approach in EJA science textbooks in the city of Capanema (PA), under two aspects. As a methodological approach, this research had a qualitative approach of the science contents presented in the LDs of 7th and 9th grade of EJA. The results showed that, in general, the CTSA approach is not fully contemplated in the analyzed contents. On the other hand, the CTSA relationship with the texts covered and the activities proposed in the two WLDs were similar. However, the LDs can be improved with the re-evaluation and contemplation of a context with contents and activities that involve CTSA and its relations to the student’s daily life in a more meaningful way, contributing to the formation of critical and autonomous citizens, capable of reflecting on the various implications of their daily lives.